Fracture of Lateral end of Clavicle with Coracoclavicular Ligament Rupture Treated with Coracoclavicular Screw and Stainless Steel Wire - A Series of Eleven Cases - Chaudhary, Pashupati; Karn, N; Shrestha, BP; Khanal, GP; Rijal, R; Paneru, SR (Health Renaissance, 2011)
Background: Various treatment options have been described in the literature for treatment of lateral end of clavicle with no single method is superior to another. Objectives: To assess fracture stabilty, pain at fracture site and functional outcome. Methods: This is retrospective interventional (case series) study done in the department of Orthopaedics at B.P.Koirala Institue of Health Sciences, Dharan from January 2007 to December 2009 over a period of 2 years.The study enrolled 11 patients aged 18-35 years who had presented with fracture lateral end of clavicle. All patients underwent open reduction and internal fixation of fractures with coracoclavicular screw and stainless steel wire. Results: The study was comprised of 8 men and 3 women. Average patient.s age was mean ±SD 27.2 years (range: 18-35 years). The common mechanism of injury was a fall on outstretched hand with the shoulder in extension and abduction (6 patients) followded by direct violence (5 patients). Most of the patients were right handed. All patients were returned to the pre-injury work level with no pain or dysfunction. There was no pseudoarthrosis, infection, neurovascular damage, or skin necrosis or implant failure. Conclusion: Coracoclavicular screw/ SS wire fixation is a relatively simple, reliable, and safe technique of indirect open reduction and internal fixation of the type II distal clavicle fracture with a low complication rate. Key words: clavicle; coracoclavicular screw; steinless steel wire DOI: 10.3126/hren.v8i3.4206 Health Renaissance, September-December 2010; Vol 8 (No.3);147-151